Enhancement of carotenoid and chlorophyll content of an edible freshwater alga (Kai: Cladophora sp.) by supplementary inorganic phosphate and investigation of its biomass production - Taweesak Khuantrairong (2018)
Enhancement of the carotenoid and chlorophyll content of an edible freshwater alga (Kai: Cladophora sp.) by supplementary inorganic phosphate in canteen wastewater was investigated. The mass cultivation of the alga was conducted at ambient temperature and light intensity in diluted canteen wastewater enhanced with dipotassium hydrogen phosphate at 5-20 mg L -1. An increase in total carotenoid and chlorophyll was observed. However, it had no effect on biomass production. As a result of the algal cultivation, there was a dramatic improvement in the quality of canteen wastewater. © 2012 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.